Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Motivasi Kerja terhadap Kepuasan Kerja serta Implikasinya pada Kinerja Guru - Achmad Badawi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2014)
The purpose of this study was to obtain empirical evidence and to determine the phenomenon transparently and conclusions about the effect of the work environment, work discipline and motivation on job satisfaction and its implications for teacher performance. The research method using descriptive analysis and verification, with data analysis techniques using Path Analysis. Using probability sampling with proportional stratified cluster random sampling, with a sample size of 248 samples. The results showed that the working environment conditions that are in both criteria, conditions of work discipline of teachers at both criteria criteria, conditions and motivate the teachers were on good criteria, conditions job satisfaction, are on good criteria, and the condition of teacher performance, are in good criteria. There are later proved significant influence of the working environment to the satisfaction of the Master, There is a significant influence on the discipline of work toward satisfaction, there is a significant effect of work motivation on teacher satisfaction. Simultaneously there is a significant influence of the work environment, work discipline and motivation of teachers to work satisfaction of teachers, with the magnitude of the effect of 69.80 percent, while the influence of other variables outside the model (ε1) amounted to 30.20%. And there is significant influence of satisfaction on the performance of teachers, with the magnitude of the effect of 79.30 percent, while the influence of other variables outside the model (ε2) amounted to 20.70 percent.